Immunobiology of Uveal Melanoma: State of the Art and Therapeutic Targets - Basile, Maria Sofia; Mazzon, Emanuela; Fagone, Paolo; Longo, Antonio; Russo, Andrea; Fallico, Matteo; Bonfiglio, Vincenza; Nicoletti, Ferdinando; Avitabile, Teresio; Reibaldi, Michele (Frontiers in Oncology, 2019)
Uveal Melanoma (UM) represents the most common primary intraocular malignant tumor in adults. Although it originates from melanocytes as cutaneous melanoma, it shows significant clinical and biological differences with the latter, including the high resistance to immune-therapy. Indeed, UM is able to evade immune surveillance via multiple mechanisms, such as the expression of inhibitory checkpoints (e.g. PD-L1, CD47, CD200), production of IDO-1 and soluble FasL, among the others. More in depth understanding of these mechanisms will suggest potential targets for the design of novel and more effective management strategies for UM patients.